ANALISIS PENAMBAHAN SERAT JERAMI TERHADAP KARAKTERISTIK KUAT TARIK KOMPOSIT FRP (FIBER REINFORCEMENT PLASTIC) - Nuraini L usi; Anggra Fiveriati; Siska Aprilia H; Arif Pungga Irawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
This aims of this research is to determine the mechanical characteristics of composite materials from one of organic fibers that have environmentally friendly properties and widely available in the territory of Indonesia. The organic fiber studied in this research was rice straw, the characteristics to be studied were tensile strength by tensile testing and adjusted to ASTM standard (American Standards of Test Materials). The composite / composite paneling is made by hand lay up and with manual emphasis using glass as a mold and press. Composition of the test material (composite) ie the volume of rice straw by 35%, 64.5% resin volume and 0.5% catalyst volume. The variables of this study are the length of fiber 15 mm, 20 mm and 25 mmm, the direction of fiber angle 00 ,450 and 900 . Another variable is the length of soaking fiber with alkali. Based on the mechanical characteristics of organic fibers, it is obtained that the rice straw fiber which has the best tensile strength characteristic is by the immersion treatment among other variations. Keywords: composite, rice straw, FRP